Numerical analysis and optimization : an introduction to mathematical modelling and numerical simulation - Allaire, Grégoire (Numerical mathematics and scientific computation., 2007)
This work familiarises students with mathematical models (PDEs) and methods of numerical solution and optimisation. Including numerous exercises and examples, this is an ideal text for advanced students in Applied Mathematics, Engineering, Physical Science and Computer Science.